Les conditions de la confiance entre gestionnaires et représentants syndicaux dans un contexte d’innovations - Laplante, Normand; Harrisson, Denis (Relations industrielles / Industrial Relations, 2008)
Cet article analyse les conditions associées au développement de la relation de confiance entre les gestionnaires et les représentants syndicaux au sein d’entreprises qui ont adopté des innovations de différentes formes. Nous nous intéressons à la confiance entre des agents qui interviennent au nom de commettants. Notre étude démontre que si le développement de la confiance bénéficie d’un climat de travail moins conflictuel, d’autres conditions sont également requises, particulièrement le partage des informations entre les parties. Par ailleurs, un contexte de transformation peut améliorer la relation de confiance, particulièrement lorsqu’un processus participatif confiant un rôle au syndicat est adopté pour introduire les innovations. Celles-ci peuvent ainsi favoriser le développement de la confiance cognitive entre les parties, tout en respectant des intérêts spécifiques à chacune., This article examines the development of relationships of trust between managers and union representatives in a context of social innovations. Trust acts as a social lubricant and thus plays an important role in social relations within organizations undergoing change and which depend more on cooperation. However, trust is a multidimensional concept that appears in various forms that can be dichotomized between cognitive trust, which is based more on knowledge and reason, and identity-based trust, which is more emotional and may even involve holding common values. Within organizations, studies of trust have most often examined relations between workers and managers, or even members’ trust in their organization. Few studies have examined the relationship of trust between employers and unions. However, the interactions between institutional agents at work tend to encourage the development of the cognitive dimension of trust rather than its identity-based dimension. While encouraging cooperation between these agents and leading them to develop new relationships outside the traditional institutional framework, innovation nevertheless conceals two essential conditions for the development of trust: the interdependence of actors, and risk in the face of the future and unknown behaviour of their counterpart. Trust is not a given, but is rather a social construction that develops through the interactions of the actors at work according to the diverse conditions that we will examine. The data come from a study on new work relations between employers and unions. The sample includes union representatives and managers in goods and services firms that adopted different kinds of innovations. One thousand firms, each with more than 50 workers, were included in the study. A total of 242 union representatives and 221 managers returned their questionnaires. The sample was generally characterized by medium- or large-sized firms with a high proportion of male workers occupying permanent positions and with several years of seniority. However, there are differences between manufacturing sector firms and services sector firms. The latter employ more women who are less likely to have permanent positions and who have fewer years of seniority. Trust was measured using the average of four dimensions of the Butler scale: integrity, discretion, promise of results, and overall trust. The alpha coefficient of this trust indicator is 0.93 for both union representatives and managers. A second dependent variable measures the improvement in the trust relationship following the adoption of the innovation that the respondent considers to be the most significant. The two dependent variables (trust relationship and improvement of this relationship) have been analyzed using multiple regression and according to a model that includes several dimensions: socio-demographic characteristics, socio-economic context, labour relations climate, access to information, types of innovations, implementation process for innovations and their impacts. The union representatives indicated a lower level of trust (3.15 vs. 3.81/5) and fewer of them believe that trust increased following the adoption of the most significant innovation (27% vs. 44%). The differences between the union representatives and managers remain significant, after adjustment for different dimensions of the analytical model. This shows that the relationship is asymmetrical: the union representatives have less control over the situation and feel more vulnerable to potential opportunistic behaviours on the part of their management counterpart. Nevertheless, both the trust relationship and its improvement following the adoption of the most significant innovation are influenced by different dimensions of the analytical model. First of all, both the managers and the union representatives in the manufacturing sector are less likely than those in the services sector to feel trust. Trust is not highly related to the socio-economic context, although managers have more trust when the work force is declining; the trust of union representatives is lower when subcontracting increases. Trust is influenced by the labour relations climate. Thus trust is lower when there are more grievances or when grievances are increasing. However, trust is stronger when grievances tend to be resolved internally. Trust is also higher when respondents have access to the information requested from their counterpart. Innovations also influence trust, which is lower following the adoption of monetary innovations, but higher when other types of innovations are adopted: labour relations, work organization, training. The process of adopting innovations is important for improving the trust relationship, both when they are adopted to respond to human factors rather than factors linked to productivity, as well as when they are established through a negotiation process and a joint monitoring mechanism. Finally, negative impacts decrease trust while positive impacts do not influence the relationship of trust between union representatives and managers. The study revealed the factors that can favour the development of a relationship of trust between union representatives and managers following the adoption of social innovations. The process of adopting these innovations rather than the type of innovations seems to have a more important impact on the improvement of the trust relationship. However, this development should not be seen as an automatic transposition of the trust relationship to other members of the organization. Another question to be addressed is to what extent trust can be built without the parties losing their own identity. Our results support those of other studies that seem to show that although the cognitive dimension of trust can be developed readily between the agents at work, this is not true of identity-based trust., Este artículo analiza las condiciones asociadas al desarrollo de la relación de confianza entre directivos y representantes sindicales al interior de empresas que han adoptado diferentes formas de innovaciones. Nos interesamos a la confianza entre agentes que intervienen en nombre de comitentes. Nuestro estudio demuestra que si el desarrollo de la confianza beneficia de un clima de trabajo menos conflictivo, otras condiciones son igualmente requeridas, particularmente el hecho de compartir las informaciones entre las partes. De otro lado, un contexto de transformación puede mejorar la relación de confianza, particularmente cuando se adopta un proceso participativo para introducir las innovaciones, confiando así un rol al sindicato. De esta manera, estas innovaciones pueden favorecer el desarrollo de la confianza cognitiva entre las partes sin dejar de respetar los intereses específicos de cada uno.